Adapting First World Blended Learning Models for ELT in Bangladesh: A Policy and Practice Framework - Chand, Md. Chand Ali; Mostak, Mostak Hossain (International Journal of Language and Literary Studies, 2026)
This study aims to explore how First World mixed-model blended learning practices can strengthen English Language Teaching (ELT) in Bangladesh. Using a comparative, evidence-based methodology, it analyzes norms and policies, infrastructural readiness, pedagogical processes, teacher training, and assessment patterns from five developed nations—the United States, the United Kingdom, Canada, Australia, and Finland—and evaluates their suitability for the Bangladeshi context. Data were drawn almost from almost 36 documented implementation processes, institutional readiness reports, and digital equity studies. Data were drawn from 36 documented implementation processes, institutional readiness reports, and digital equity studies. The study argues that effective ELT-oriented blended learning rests on five core pillars, including a supportive national policy, adequate infrastructure, localized learning content, strong teacher capacity development, and innovative formative assessment. Despite persistent challenges in infrastructure and teacher readiness in Bangladesh, the research indicates that targeted interventions, such as pilot programs in urban areas, public-private partnerships, and focused professional development, can yield realistic improvements. The study, therefore, proposes a context-specific National Blended Learning Framework and outlines practical implications for policymakers, educators, and institutions seeking to reduce global-local disparities and enhance equity, engagement, and English proficiency.